1993
DOI: 10.3109/08923979309026001
|View full text |Cite
|
Sign up to set email alerts
|

Triazolobenzodiazepines Exert Immunopotentiating Activities on Normal Human Peripheral Blood Lymphocytes

Abstract: Previous studies have demonstrated that benzodiazepines (BDZ) (e.g. diazepam) inhibit immune responsiveness. Since these drugs are largely used in psychiatric patients it is of great importance to verify the existence of different types of BDZ, which are not suppressive for the immune system. In this framework, our results indicate that alprazolam and triazolam, two triazolo-BDZ, do not modify in vitro phagocytosis and killing exerted by normal human polimorphonuclear cells and monocytes. On the contrary, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Speculation linking benzodiazepines to infections originally began when multiple in vivo pharmacology studies demonstrated immune dysfunction and bacterial infections of greater frequency among rodents exposed to diazepam [ 88 90 ]. Despite these results, the immunopharmacology of peripheral and central benzodiazepine GABA A receptors remains complex as other in vitro studies have shown potentiation of immune response from triazolo-benzodiazepines such as alprazolam and triazolam [ 91 93 ]. This begs the question as to whether there is a true ‘class effect’ of these agents or if there are indeed indisputable immunopharmacological differences between them.…”
Section: Infectionsmentioning
confidence: 99%
“…Speculation linking benzodiazepines to infections originally began when multiple in vivo pharmacology studies demonstrated immune dysfunction and bacterial infections of greater frequency among rodents exposed to diazepam [ 88 90 ]. Despite these results, the immunopharmacology of peripheral and central benzodiazepine GABA A receptors remains complex as other in vitro studies have shown potentiation of immune response from triazolo-benzodiazepines such as alprazolam and triazolam [ 91 93 ]. This begs the question as to whether there is a true ‘class effect’ of these agents or if there are indeed indisputable immunopharmacological differences between them.…”
Section: Infectionsmentioning
confidence: 99%
“…Alprazolam could up-regulate the depressed phagocytosis and killing in these patients, also leading to a substantial amelioration of clinical manifestations [72,73]. In these patients, the effects of Alprazolam on TNF-α release was not verified, even if this benzodiazepine has been shown to reduce LPS-induced release of TNF-α in mice [74].…”
Section: Stress-induced Modulation Of the Immune Responsementioning
confidence: 99%
“…Patients with MWA take therapeutical advantage from the use of alprazolam, a BDZ endowed with immunomodulating activities, in terms of either inhibition [71] or enhancement [72,73] of responses. Alprazolam could up-regulate the depressed phagocytosis and killing in these patients, also leading to a substantial amelioration of clinical manifestations [72,73].…”
Section: Stress-induced Modulation Of the Immune Responsementioning
confidence: 99%
“…On the contrary, the same drug does not interfere with the antibacterial activity exerted by normal human peripheral blood lymphocytes (PBL) (7). On the other hand, alprazolam and triazolarn, two triazolobenzodiazepines, markedly enhance lymphocyte-dependent antibacterial activity from normal donors, while they do not influence polymorphonuclear cell (PMN) and monocyte phagocytosis and killing (7,8).…”
Section: Introductionmentioning
confidence: 99%